CONSTRUCTION OF MIDDLE SCHOOL STUDENTS (SMA) AGAINST POLITICAL EDUCATION (Phenomenology Study of State High School 3 Malang Students) - Agus, Basuki (Journal of Local Government Issues, 2019)
AbstractAn interesting phenomenon appears related to the relationship between high school students, schools, parents, and the government. The relationship between students and school raises the tendency for more students to spend more time at school. Besides, the majority of parents intensively encourage their children to engage in physical and organizational activities, even to conduct 'politics' in the school environment. Another phenomenon shows that the government has made several efforts, including in political affairs, to prepare students to become citizens as a whole. This paper uses a phenomenological approach to describe and understand the construction of high school students towards political education. In addition, in theory, this research was conducted to find propositions related to the development of political education. This study uses a qualitative model by taking the locus in the Intra-School Student Organization (OSIS) and Class Representative Chair (PK) of SMAN 3 Malang. As informants are teachers of Parental Education and parents. This research shows that the construction of high school students towards political education is in the form of political education concepts, implementation, objects, and their benefits. In the operational stage of Piaget's intelligence, the construction pattern is as follows: external environmental pressure, reflective, incomplete, fumbling and assimilating. Furthermore, based on the theory of Berger and Luckmann, the construction of political education of students follows dialectics with moments of externalization, objectivation, internalization, socialization, and resocialization to form knowledge reserves.Keywords: Students, political education, SMAN 3 Malang